Експериментальний підхід до створення ефективного багатокомпонентного нанокомпозита для протипухлинної терапії - Kutsevol, N.; Kuziv, Y.; Chumachenko, V.; Nadtoka, O.; Bulavin, L.; Chekhun, V. (Publishing house "Academperiodika", 2020)
Water-soluble polymers with special characteristics can be used as carriers in which the active ingredients are entrapped, encapsulated, adsorbed, or chemically attached. The understanding of the processes occurring during the formation of multicomponent nanosystems is the urgent task for the synthesis of antitumor nanocomposites. Gold nanoparticles (AuNPs), photosensitizer Chlorine e6 (Ce6), and Doxorubicin (Dox) are currently used for the photodynamic therapy and chemotherapy. We have been focused on the study of three-component nanosystems Polymer/AuNPs/Ce6, and four-component nanosystems Polymer/AuNPs/Ce6/Dox at physiological temperatures (37 ∘C). The star-like copolymer with Dextran core and grafted Polyacrylamide chains in nonionic and anionic forms are used as a matrix for the synthesis of nanocomposites. The nanosystems are characterized by the dynamic light scattering and transmission electron microscopy. The increasing of the aggregation processes for the four-component nanosystem Polymer/AuNPs/Ce6/Dox in comparison with the three-component one Polymer/AuNPs/Ce6 is registered. These nanosystems are tested in vitro against the subline of breast carcinoma MCF-7/S – sensitive to cytostatics. It is demonstrated that the increase of the aggregation process occurring in four-component systems leads to the loss of the antitumor activity of multicomponent drugs.